2007
DOI: 10.1038/sj.ki.5002112
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mammalian target of rapamycin impedes lymphangiogenesis

Abstract: Lymphatic complications are common side effects of mammalian target of rapamycin (mTOR) inhibitor-based immunosuppression in kidney transplantation. Therefore, we investigated whether the mTOR inhibitor rapamycin, besides its known antihemangiogenic effect, also impedes regenerative lymphangiogenesis. In a murine skin flap model, rapamycin impaired recovery of lymphatic flow across surgical incisions resulting in prolonged wound edema in these animals. Importantly, the antilymphangiogenic effect of rapamycin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(137 citation statements)
references
References 20 publications
3
129
1
4
Order By: Relevance
“…These classical methods of treatment have their limitations, hence the popularity of incorporating sirolimus in the therapeutic regimen of complex cases had risen. Consequently, the side effects which have been noted in different populations such as bone marrow suppression in kidney transplant patients is now becoming more evident in LM populations treated with the sirolimus [3]. In this case series, we corroborate with what has been reported on sirolimus as an effective therapeutic regimen in the treatment of lymphatic malformation.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…These classical methods of treatment have their limitations, hence the popularity of incorporating sirolimus in the therapeutic regimen of complex cases had risen. Consequently, the side effects which have been noted in different populations such as bone marrow suppression in kidney transplant patients is now becoming more evident in LM populations treated with the sirolimus [3]. In this case series, we corroborate with what has been reported on sirolimus as an effective therapeutic regimen in the treatment of lymphatic malformation.…”
Section: Introductionsupporting
confidence: 88%
“…Different therapeutic methods like surgical excision: the first line of treatment; and the non-surgical methods which include sclerotherapy, laser, aspiration, and radiotherapy have been proposed [3]. These classical methods of treatment have their limitations, hence the popularity of incorporating sirolimus in the therapeutic regimen of complex cases had risen.…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) pathway has recently been identified to function in lymphangiogenesis. mTOR inhibition by rapamycin showed specific anti-lymphangiogenic effects in mammalian experimental systems (Huber et al, 2007;Kobayashi et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have shown that mammalian target of rapamycin inhibitor is a downstream signal of vascular endothelial growth factor C and D, which are essential for lymphatic endothelial cell survival, proliferation, and migration, and that mammalian target of rapamycin inhibitor such as sirolimus can inhibit lymphangiogenesis in vitro. 11,12 Chylous ascites and lymphedema in a renal transplant case were attributed to 19-month use of mammalian target of rapamycin inhibitor (eg. sirolimus), and they were relieved 1 month after switching to cyclosporine.…”
Section: Discussionmentioning
confidence: 99%